2015
DOI: 10.1007/s10725-015-0095-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of WRKY genes in di-haploid Populus simonii × P. nigra in response to osmotic stress and ABA treatment

Abstract: In this study, 108 WRKY genes with complete conserved WRKY domain and zinc-finger motif were identified from poplar in silico, and they were classified into three subfamilies named I, II, and III. The WRKY members in group II were further clustered into five subgroups (IIa-e), where members in group I and III formed a single cluster. Thirteen highly expressed genes were employed to profile their spatio-temporal expression patterns in response to osmotic stress and ABA treatment by qRT-PCR. Under both osmotic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…The latest release of the PlantTFDB (http://planttfdb.cbi.pku.edu.cn/)transcription factor database contains a total of 185 Populus tomentosa WRKYs. Over a dozen related transcription factors have been isolated, their functions have been verified [25], and the WRKY family genes in many poplar trees have been shown to respond to abiotic stress and play important roles in salt resistance [26][27][28]. Preliminary laboratory research revealed that PeWRKY31 of Populus × euramericana responded to biological stress, but the underlying mechanism was not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The latest release of the PlantTFDB (http://planttfdb.cbi.pku.edu.cn/)transcription factor database contains a total of 185 Populus tomentosa WRKYs. Over a dozen related transcription factors have been isolated, their functions have been verified [25], and the WRKY family genes in many poplar trees have been shown to respond to abiotic stress and play important roles in salt resistance [26][27][28]. Preliminary laboratory research revealed that PeWRKY31 of Populus × euramericana responded to biological stress, but the underlying mechanism was not clear.…”
Section: Introductionmentioning
confidence: 99%